Heritage language use in the country of residence matters for language maintenance, but short visits to the homeland can boost heritage language outcomes - Chondrogianni, Vasiliki; Daskalaki, Evangelia (Frontiers in Language Sciences, 2023)
This study examined how heritage children’s experiences with the heritage language (HL) in the country of residence (e.g., children’s generation, their HL use and richness) and the country of origin (e.g., visits to and from the homeland) may change as a function of the migration generation heritage children belong to, and how this may in turn differentially influence HL outcomes. 58 Greek-English-speaking bilingual children of Greek heritage residing in Western Canada and New York City participated in the study. They belonged to three different generations of migration: a group of second-generation heritage speakers, which were children of first-generation parents; a group of mixed-generation heritage children of first- and second-generation parents; and of third-generation heritage children with second-generation parents. They were tested on a picture-naming task targeting HL vocabulary and on an elicitation task targeting syntax- and discourse-conditioned subject placement. Children’s performance on both tasks was predicted by their generation status, with the third generation having significantly lower accuracy than the second and the mixed generations. HL use significantly predicted language outcomes across generations. However, visits to and from the country of origin also mattered. This study shows that HL use in the country of residence is important for HL development, but that it changes as a function of the child’s generation. At the same time, the finding that the most vulnerable domains (vocabulary and discourse-conditioned subject placement) benefited from visits to the country of origin highlights the importance of both diversity of and exposure to a variety spoken by more speakers and in different contexts for HL maintenance.